2021
DOI: 10.52547/rbmb.10.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Sexually Transmitted Infections in Women with and without Human Papillomaviruses Infection Who Referred to Tehran West Hospitals in Iran

Abstract: Background:According to the studies, many pathogens function as cofactors interacting with Human papillomavirus in the development of pre-cancer or cancer of the cervix. The aim of this study was to investigate the prevalence rate of Sexually Transmitted Infections (STIs) pathogens including Mycoplasma hominis, Ureaplasma urealyticum, Chlamydia trachomatis, Neisseria gonorrhoeae, Gardnerella vaginalis, and Streptococcus agalactiae in people with HPV and without HPV infection, and frequency rate of these pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…The rate of M. hominis infection was 21% in the current study which agreed with results of Majhi et al (2022) who found that 20% of sexually active women were positive, while lower than the results of Fatlawy and Abduljabbar (2019) who found that 31.12% of the infertile women from Iraq were positive. On another hand, these results were higher than the results of Mortazavi et al (2021) in Iran who found that 7.62% of the infertile women were positive.…”
Section: Results Of Multiplex Real-time Pcr Techniquecontrasting
confidence: 63%
See 1 more Smart Citation
“…The rate of M. hominis infection was 21% in the current study which agreed with results of Majhi et al (2022) who found that 20% of sexually active women were positive, while lower than the results of Fatlawy and Abduljabbar (2019) who found that 31.12% of the infertile women from Iraq were positive. On another hand, these results were higher than the results of Mortazavi et al (2021) in Iran who found that 7.62% of the infertile women were positive.…”
Section: Results Of Multiplex Real-time Pcr Techniquecontrasting
confidence: 63%
“…Among tested infertile women for U. urealyticum, 16.0% were positive. The results were lower than those by Fatlway and Abduljabbar (2019) who found that 26.81% of infertile women from Baghdad, Iraq were positive, and in Iran by (Peerayeh et al, 2006) (Mortazavi et al, 2021) who found that 30.7% and 38.13% of the infertile women were positive for this pathogen respectively.…”
Section: Results Of Multiplex Real-time Pcr Techniquementioning
confidence: 58%
“…GV is typically found at pH > 4.5 which may be a result of the decrease of estrogens and progestin favoring the infection and survival of GV 69,70 . Our result is controversial since different authors have linked a potential impact of GV in the development of cervical lesions and/or cancer while others fail to show any association 68,71–73 . Furthermore, some authors have been showing that quantification of some microorganisms such as GV may be of potential interest, which should be further explored 74 …”
Section: Discussionmentioning
confidence: 74%
“…69,70 Our result is controversial since different authors have linked a potential impact of GV in the development of cervical lesions and/or cancer while others fail to show any association. 68,[71][72][73] Furthermore, some authors have been showing that quantification of some microorganisms such as GV may be of potential interest, which should be further explored. 74 Regarding other common agents, we found that MH (p = 0.028; RR = 1.51) and Mob were highly associated with HPV-9val (p = 0.025; RR = 1.85).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation